Pilotní výzkum v etnografii: Bariéry v interakci mezi Romy a majoritou - Vavroch, Michal (Lidé města, 2014)
This article discusses the importance of a pilot study when undertaking qualitative inquiry. One of the fundamental characteristics of qualitative research is the emerging design. This means that research question(s) may be adjusted, the methodology of data collection modified and the place changed after entering the field. The paper presents my own experience with the transformation of a research design during the research process. The subject of my research was the interaction between the Roma and the majority population, which I decided to investigate through the ethnographic approach. The necessary preliminary analysis was conducted. However, after entering the field, I discovered that the research agenda was in conflict with the nature of the environment. It was necessary to find a new line of inquiry which took me a considerable amount of time. The question is whether it could be avoided by a pilot study implementation. In order to assess the role of this method, I created a virtual pilot study. It presents, in detail, the specific procedures used and their utilization. Although my field activities met a number of parameters of the pilot study, the main point was not implemented – a fundamental change in the research design. The purpose of this paper is to initiate a discussion on the usefulness of a pilot study in ethnography. It could be interesting especially for beginning researchers, and / or for those wishing to do research in hard-to-reach groups. The text itself is written in reflexive form. It also suggests some of the findings related to the theoretical grasp of the Roma identity and identification.